The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s13014-015-0377-9
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy was associated with a higher severe late toxicity rate in nasopharyngeal carcinoma patients compared with radiotherapy alone: a meta-analysis based on randomized controlled trials

Abstract: BackgroundTo investigate the incidence and risk of severe late toxicity with concurrent chemoradiotherapy (CCRT) in nasopharyngeal carcinoma patients.MethodsEligible studies included prospective randomized controlled trials (RCTs) evaluating CCRT versus radiotherapy alone in patients with nasopharyngeal carcinoma and in which data on severe late toxicities were available. Random effects or fixed effect models were applied to obtain the summary incidence, relative risks (RRs) and 95% confidence intervals (CIs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 25 publications
0
32
1
Order By: Relevance
“…[5][6][7] Cisplatin and irradiation are known to be toxic to hearing and ototoxicity remains one the most commonly encountered late toxicities for NPC patients treated by CCRT. 25 The incidence rate of developing severe (grade 3 or more) ototoxicity in our series is low (4 year cumulative incidence rate: 3.0%), which was non-inferior to other NPC series treated by CCRT with SIB-VMAT (0%), 26 or CCRT with SIB-IMRT (2.0%). 23 As regards the radiation neuropathy, 1 patient (1.4%) had optic neuropathy so far, but 3 patients (4.4%) developed temporal lobe necrosis, which was mild with limited follow-up.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…[5][6][7] Cisplatin and irradiation are known to be toxic to hearing and ototoxicity remains one the most commonly encountered late toxicities for NPC patients treated by CCRT. 25 The incidence rate of developing severe (grade 3 or more) ototoxicity in our series is low (4 year cumulative incidence rate: 3.0%), which was non-inferior to other NPC series treated by CCRT with SIB-VMAT (0%), 26 or CCRT with SIB-IMRT (2.0%). 23 As regards the radiation neuropathy, 1 patient (1.4%) had optic neuropathy so far, but 3 patients (4.4%) developed temporal lobe necrosis, which was mild with limited follow-up.…”
Section: Discussioncontrasting
confidence: 48%
“…In addition to parotid sparing, SIB‐VMAT also provides dosimetric benefits in the critical structures of skull base, temporal lobe, and ear structure for NPC planning . Cisplatin and irradiation are known to be toxic to hearing and ototoxicity remains one the most commonly encountered late toxicities for NPC patients treated by CCRT . The incidence rate of developing severe (grade 3 or more) ototoxicity in our series is low (4 year cumulative incidence rate: 3.0%), which was non‐inferior to other NPC series treated by CCRT with SIB‐VMAT (0%), or CCRT with SIB‐IMRT (2.0%) .…”
Section: Discussionmentioning
confidence: 65%
“…Therefore, radiotherapy plays an important role in the treatment of NPC due to its special anatomical position. 6 A strong relationship between radiotherapy and leucopenia has been reported in the literature-65.6% patients with NCP developed mild leucopenia (grade 1-2) and 21.1% developed severe leucopenia (grade 3-4) during treatment. 3 In addition, compared with radiotherapy alone, the overall 10-year survival rate of concurrent chemoradiotherapy (CCRT) is significantly improved.…”
Section: Introductionmentioning
confidence: 93%
“…5 Study showed that the incidence of side effects of CCRT was significantly higher than that of radiotherapy alone (30.7% vs 21.7%). 6 A strong relationship between radiotherapy and leucopenia has been reported in the literature-65.6% patients with NCP developed mild leucopenia (grade 1-2) and 21.1% developed severe leucopenia (grade 3-4) during treatment. 7 Till date, most studies on oral nutrition supplementations (ONS) of patients with NCP during CCRT focused on improvement of nutritional status, 8 whereas information is lacking on prevention of myelosuppression which could profoundly affect the progress of CCRT immediately, and even lead to the termination of treatment.…”
Section: Introductionmentioning
confidence: 93%
“…Concurrent chemoradiotherapy (CCRT) is the standard treatment for locoregional advanced NPC (LA-NPC) 3,4. Unfortunately, CCRT is associated with significant treatment-related toxicities, including mucositis, odynophagia, dysphagia, xerostomia, and vomiting 5,6. These complications can put patients at risk of malnutrition, thereby compromising treatment tolerance and efficacy, and increasing health care costs 7.…”
Section: Introductionmentioning
confidence: 99%